Information Technology and Libraries - Library and Information Technology Association (U.S.) ([Chicago, IL] : [Library and Information Technology Association], 1982)
Print only
Keywords: Information science -- Periodicals; Libraries -- Automation -- Periodicals; Information Systems -- Periodicals; Libraries -- Periodicals